STRATEGI PEMILIHAN SUPPLIER YANG TEPAT PADA INDUSTRI PULP & PAPER - Kaidah, Sri; Purnamasari, Mega (Politeknik ATI Padang, 2022)
One of the pulp & paper industries in Banten differentiates between several suppliers based on fixed contract cooperation for main raw materials and irregular contracts for supporting raw materials. Cooperation with variable contracts often causes problems such as delays in delivery, product specifications and quantities of goods that do not match the ones ordered. This is because companies in selecting suppliers for non-fixed contracts still use conventional selection methods by determining criteria based only on price and quality of goods, but not based on consideration of other criteria or those that suit the company's needs. This often interferes with the progress of production process activities. The Analytical Hierarchy Process (AHP) method is used to solve problems that occur as a strategy to determine the right criteria and suppliers. From the results of the analysis carried out using the Analytical Hierarchy Process (AHP) method, it was found that the priority value of the Price criterion is 0.18; Shipping is 0.41; Quality is 0.28; and Responsiveness is 0.13. From the results of comparative weighting at the hierarchy level of the criteria, it was found that the highest priority value was on the delivery criteria of 0.41. With the best supplier is PT. A that gets a weighted value of 0.41; while the other two suppliers are PT. B receives a weighted value of 0.36 and PT. C of 0.22.